Innovation and integration: Analysis of research hotspots and frontiers in "Chinese + vocational skills" education—based on bibliometric analysis visualized by citespace - Zhao, Yan; Liu, Zhenping (Edelweiss Applied Science and Technology, 2024)
The "Chinese + Vocational Skills" education is a new form of education merging international Chinese education with vocational training. This paradigm has emerged as a focal point in research on international Chinese language education. This article is aimed to effectively dissect the developmental patterns and prevailing research topics on "Chinese + Vocational Skills", by employing CiteSpace, a tool for visualizing scientific data, to analyze pertinent literature spanning the last decade (2013–2023). The analysis offers insights into the overall landscape and evolutionary trajectory of research in this field. The findings therefrom indicate the followings: (1) Research on "Chinese + Vocational Skills" exhibits certain interdisciplinary characteristics, with an overall trend of rapid growth in research literature, but a relatively small volume of high-quality core literature. (2) "International Chinese Language Education", "Vocational Education", "Chinese + Vocational Skills", and the "Belt and Road" are current research hotspots in this field. "Chinese +",Chinese for Specific Purpose, demand analysis, and vocational skills serve as important turning points for research on "Chinese + Vocational Skills". (3) Research topics related to "Chinese + Vocational Skills" mainly concentrate on four aspects: international Chinese language education, vocational education, talent cultivation, as well as regions and countries, yet disparities of research endeavors exist across these fields. (4) The research frontier of the field mainly focuses on international Chinese language education, "Chinese + Vocational Skills", international vocational education on Chinese language in vocational colleges, and internationalization of Chinese language. Addressing contemporary demands, research in "Chinese + Vocational Skills" needs to align with global economic trends, cater to the actual needs for talent with such skills, and further enhance understanding from various perspectives including educational models, national demands, and internationalization efforts, thus fortifying the capacity of "Chinese + Vocational Skills" education to serve the development of industries.